ENKAPSULASI CAMPURAN MINYAK ATSIRI SEBAGAI PRODUK SEDIAAN AROMATERAPI DENGAN TEKNIK KOASERVASI KOMPLEKS - Annisa Putri; Meika Syahbana Rusli; Dwi Setyaningsih (Jurnal Teknologi Industri Pertanian, 2020)
Essential oils are used as raw materials in the flavors and fragrances industry. Essential oils contain active compounds that are volatile at ambient temperature so that it is unstable to environmental changes. Complex coacervation is one of the techniques used in the encapsulation process to protect the active material. Essential oil blends were encapsulated by gelatin and maltodextrin as wall material and sodium tripolyphosphate as crosslinking agent. The objective of this study was to analyze the effect of the proportion between essential oils, wall material, and crosslinking agents on the yield, loading capacity, and encapsulation efficiency. The results showed that the optimum formulation for microcapsules was the essential oil and wall material ratio 1:2 and crosslinking agent concentration of 3%, with the yield of 45.18%, loading capacity of 5.37%, and encapsulation efficiency of 92.20%. The microcapsule size obtained was 0.1475 μm with polydispersity index of 0.410. Key words: complex coacervation, encapsulation, essential oil, gelatin, maltodextrin